The Snow Queen - Mackinnon,Mairi; Sellivanova,Elena (London usborne publishing, 2019)
Usborne story books retell stories that children know and love, in a way that really builds their confidence in reading for themselves, at the back of the book there are activities and talking points
English stories
Keywords: English stories